The non-linear impact of digital trade development on carbon emissions: Evidence from Chinese cities - Xiangxiang Zhou; Hui Guo (Energy Nexus)
The development of digital trade has emerged as a significant driver of global carbon reduction. Based on panel data from 257 Chinese cities between 2013 and 2019, this paper investigates the relationship between the development of urban digital trade and carbon emissions in depth. The analysis reveals an inverted U-shaped relationship between digital trade and carbon emissions: during the early stages of digital trade development, carbon emissions increase, but after reaching a certain threshold, carbon emissions gradually decline. This conclusion remains robust following endogeneity tests. Further examination indicates that the market integration plays a dynamic moderating role in this relationship: a higher market integration flattens the inverted U-shaped curve and shifts the inflection point to the left, meaning that the positive impact of digital trade on carbon emission reduction occurs at an earlier stage. Additionally, the study highlights that varying levels of industrial structure, green innovation, and digital infrastructure exert heterogeneous effects on the inverted U-shaped relationship. Specifically, cities with higher levels of industrial structure, green innovation, and digital infrastructure tend to enter the carbon emission reduction phase earlier. These findings provide important insights for policymakers seeking to balance the growth of digital trade with environmental sustainability, especially in the context of tailoring differentiated policies according to the unique environmental conditions of different cities, thereby promoting the synergistic development of digital trade and carbon reduction.